Electrical properties and memory applications of Al-rich Al-based dielectric thin films - Zhu, Wei (2013)
An AI-rich Al203 thin film was deposited on a p-type silicon substrate by rf sputtering to form AIIAI-rich AI20 3/p-Si diodes. The current-voltage (I-V) characteristics of the diodes were determined by carrier injection from either the Si substrate or the Al gate and by carrier transport along the tunneling paths formed by Al nanocrystals distributed in the oxide layer. The reverse IV characteristics were greatly affected by the charge trapping in the oxide layer, Le., the electron trapping significantly reduced the reverse current while the hole trapping enhanced the current significantly. However, the charge trapping did not produce a large change in the forward I-V characteristic. A write-once-read-many memory (WORM) device was realized based on the chargingcontrolled modulation in the current conduction of AIIAI-rich AI203/p-Si diode. A large increase in the reverse current of the diode could be achieved with a negative charging voltage, e.g., charging at -25 V for 1 ms resulted in a current increase by about four orders. Memory states of the WORM device could be altered by changing the current conduction with charge trapping in the AI-rich Al203 layer. The memory exhibited good reading endurance and retention characteristics. Metal-insulator-metal (MIM) structure was fabricated by partially anodizing aluminum film followed by deposition of another aluminum film. Unipolar resistive switching between a highresistance state and a low-resistance state with a high resistance ratio (>--104) was observed from the structure. The switching occurred without the requirement of a forming process, which was attributed to the pre-existing conductive filaments in the AI-rich Al.O; layer formed by the anodization. Each resistance state exhibited ohmic behavior which could be explained by the metallic conduction and electron hopping from one isolated state to the next in the AI-rich Al.O; layer. The MIM structure showed good memory characteristics. AIOxNy dielectric thin films have been synthesized with rf sputtering of Al target in the presence of a mixture of oxygen and nitrogen. The electrical properties of the MIM and MIS structures based on the AIOxNy dielectric thin films have been studied. It was observed that the MIM structure showed multiple resistive switching. The resistive switching strongly depended on the oxygen concentration, and it did not occur if the oxygen concentration was very low, highlighting the important role of oxygen. On the other hand, the current conduction in the MIS structure was found to be affected by the charge trapping in the dielectric films.